DEPRESIÓN Y SU RELACIÓN CON LA FUNCIONALIDAD FAMILIAR EN ADOLESCENTES DEL COLEGIO VIRGEN DEL CARMEN AREQUIPA-2021 - Medina Sanchez, Alexis Marcelina (2022)
Objective: To determine the relationship between depression and family functionality in adolescents from Colegio Virgen del Carmen Arequipa 2021. Material and method: Study of a quantitative non-experimental correlational type, of a correlational level and a non-experimental design, the population was 200 adolescents to whom the Hamilton and Apgar depression scale was applied. The results were presented descriptively in chapter V and VI. Results: It was corroborated that 32% of adolescents present moderate depression and 35% of adolescents showed mild dysfunction within their family nucleus, characterized by a lack of empathy, understanding and sensitivity towards certain family members, while that, on the other hand, the expression of extreme empathy towards one or more family members (or even pets) who have "special needs" (real or perceived), there is also a lack of time-sharing, especially in recreational activities and social events. Conclusions: There is a relationship between depression and family functionality in adolescents from Colegio Virgen del Carmen Arequipa 2021, since the Rho Spearman value obtained is 0.835 ** which determines a strong positive correlation; among the variables studied. Therefore, the lower the depression, the greater the family functionality. Keywords: depression, family functionality, anxiety, adolescents.